2006
DOI: 10.1007/s10800-006-9139-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Cu from Acidic Sulphate Solutions in the Presence of PEG: An Electrochemical and Spectroelectrochemical Investigation – Part I

Abstract: This paper deals with the effects of PEG during Cu electrodeposition from an acidic sulphate solution. This investigation was carried out with electrochemical and spectroelectrochemical techniques. Potentiostatically grown layers were examined by scanning electron microscopy. Adsorption of PEG on the growing Cu surface can be inferred from electrokinetic, SERS and morphological evidence: variations of the estimated exchange current density, qualitative and quantitative differences in the potentiostatic transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 48 publications
5
30
0
Order By: Relevance
“…For example, Healy & Pletcher (1998a, 1998b have shown that the studied additives (Cl -, polyethylene glycol, and 4,5-dithiaoctane-l,8-disulfonic acid) adsorbed on the electrode at different deposition potentials and stirring speeds influences in the copper reduction mechanism. Similar results were observed by Bozzini et al (2006) and Tantavichet & Pritzker (2006), who studied the effects of polyethylene glycol and benzotriazole, respectively. Nayana et al (2011) have investigated the influence of additives on the morphology and brightness of nanocrystalline zinc electrodeposited from an acid sulfate bath.…”
Section: The Effects Of Other Deposition Parameters On the Coating Prsupporting
confidence: 87%
“…For example, Healy & Pletcher (1998a, 1998b have shown that the studied additives (Cl -, polyethylene glycol, and 4,5-dithiaoctane-l,8-disulfonic acid) adsorbed on the electrode at different deposition potentials and stirring speeds influences in the copper reduction mechanism. Similar results were observed by Bozzini et al (2006) and Tantavichet & Pritzker (2006), who studied the effects of polyethylene glycol and benzotriazole, respectively. Nayana et al (2011) have investigated the influence of additives on the morphology and brightness of nanocrystalline zinc electrodeposited from an acid sulfate bath.…”
Section: The Effects Of Other Deposition Parameters On the Coating Prsupporting
confidence: 87%
“…Within a given bath, the differences in trends can be explained in terms of the wavelength-dependence of the maxima and minima of the r(f) curves. Between baths, one can observe that the differences in behaviour between the solutions without and with PEG can be described in terms of lower f values for the latter system: this can correlate to the higher growth stability observed in the presence of the additive [1].…”
Section: R(t;k;k Ref ) Transients Can Be Interpreted In Terms Of the mentioning
confidence: 99%
“…In the first part of this series [1], we reported an electrochemical, Surface-enhanced Raman Spectroscopy (SERS) and Scanning Electron Microscopy (SEM) investigation of the effects of PEG. This paper focuses on in situ purely optical component of the absolute instantaneous reflectivity f volume fraction of metallic particles g 1 purely geometrical factor weighting reflectance g 2 wavelength-dependent geometrical factor weighting reflectance i imaginary unit Im(Z) imaginary part of a complex number Z R(k,t) absolute instanteous spectral reflectance Re(Z) real part of a complex number Z t time…”
Section: Cu Electrodepositionmentioning
confidence: 99%
See 2 more Smart Citations